Indicadores morfofisiológicos de acessos de melão cultivados sob níveis salinos - Gama, Diego Rangel da Silva (Universidade Federal Rural do Semi-Árido, 2018)
Melon is an important economic crop that has inhibited growth in saline conditions, causing structural, morphological and physiological changes and damaging productivity. Finding characteristics in plants that are tolerant to salinity is fundamental so that breeders can select promising genetic materials. Salinity is a problem that affects the growth of plants at all stages of growth and in a differentiated way, with the majority of cultivars being more sensitive during the emergence of seedlings. Thus, the objective of this work was to correlate salinity tolerance indicators during emergence of melon seedlings and to identify morphological and physiological indicators in melon plants submitted to different saline concentrations. Two experiments were carried out, one in the laboratory and the other in a greenhouse, of Federal University Rural Semi-Arid - UFERSA, Mossoró-RN, Brazil. The laboratory experiment was conducted in B.O.D. (Biochemical Oxigen Demand) from the Laboratory of Plant Ecophysiology of the CPVSA (Plant Research Center of the Semi-Arid), from March to May 2016. The design was completely randomized (DIC) (A07, A33, A32, A36, A08, A13, 2I4, 27I, 30II, 39II), and five levels of salinity (five replicates of 10 seeds), in a 10 x 5 factorial scheme. 0.0, 3.0, 6.0, 9.0, 12.0 dS m-1). The following evaluations were performed: emergency percentage (E%), emergency speed index (IVE), mean time of emergence (TME), seedling height (AP), neck diameter (DC), root length), dry matter of the stem (MSCA), dry matter of cotyledons (MSCO), dry matter of the roots (MSR). The greenhouse experiment was conducted in a protected environment with 30% shading, from August to October 2016. The experimental design was blocks with seven replicates. The treatments were arranged in a 4 x 5 factorial scheme, with the first factor consisting of the melon accessions (A07, A33, 2I4 and 39II), and the second one of the saline concentrations (0.5, 2.0, 4.0, 6.0 and 8.0 dS m-1). The experiment was carried out at 90 DAS to identify morphological indicators in the plants of the different treatments, evaluating several plant characteristics such as: stem length, stem diameter, number and length of internodes, leaf number, leaf area, leaf length and width leaf, total number of flowers, number of male and hermaphrodite flowers, root length and volume, dry matter of stem, root, leaf and total. The effect of saline levels on plants in three phenological phases of the crop, vegetative phase (35 DAS), flowering stage (55 DAS) and fruiting and senescence phase (75 DAS) were evaluated; (A; μmol CO2 m-2 s-1), plant transpiration (E; mmol H2O m-2 s-1), and internal concentration CO2 (Ci; μmol CO2 m-2 s-1), stomatal conductance of (gs; mol H2O m-2 s-1), with the aid of a LI-64 Biosciences photosynthesis meter (LI-COR Biosciences) being read between 08:00 and 10:00 AM. The anatomical characteristics of the stomata, evaluated in leaves of the accessions (A07, A33, 2I4, 39II), were also determined, in which one leaf per plant was collected with four replicates in each saline treatment. The count of the stomata by area was done on the adaxial and abaxial side of the leaves. For measurements of longitudinal and transverse diameter, two stomata of the adaxial and abaxial surfaces were taken from each sample. The results of the laboratory experiment showed that the salinity negatively affected the E%, IVE, TME, AP, CR, MSCA, MSR, except DC and MSCO characters. There was no pattern of genotype correlation coefficients between saline levels. The highest number of genotype correlations was found at the saline level with 12 dS m-1. The correlations that best indicate the tolerance of melon accessions to salinity were E% and IVE, E% and MSR, E% and MSCO, IVE and MSR, IVE and MSCO, TME and MSCO, AP and CR, AP and MSR, DC and MSCA, MSR and MSCO. The characters that best indicate the salinity tolerance are: E%, IVE, MSCO, MSR. The results of the greenhouse experiment showed that the salinity negatively affected all the growth variables of the melon accessions. The variables stem length, training length, number of leaves, leaf area, root volume, stem dry matter, leaf, root and total variables were good indicators of salinity tolerance. Access 2I4 was the most tolerant to salinity in all variables except stem length, leaf length x width, total number of flowers and number of male flowers. Physiological evaluations showed that salinity negatively affected stomatal conductance, transpiration and net photosynthetic rate only at 35 DAS, without influencing the internal CO2 concentration in the leaf. The vegetative phase at 35 DAS was the most sensitive phase to salinity. As for the stomatal evaluations, the stoma number of the adaxial and abaxial side of the leaf was reduced with increasing salinity, and the longitudinal and transverse diameters of the stomata increased with salinity
Keywords: Meloeiro; Estresse salino; Características morfológicas; Características fisiológicas; Melon; Saline stress; Morphological characteristics; Physiological characteristics; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA